Transformasi Dakwah Islam Melalui Strategi Dan Implementasi Di Era Digital - Sihabudin, Dede; Carles, Eko; Warsah, Idi; Hiptraspa, Zepri (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
In the current digital era, Islamic da'wah is facing massive transformation due to the penetration of information technology. This transformation introduced a new method of spreading Islamic teachings, which not only increased the speed and reach of da'wah, but also involved more interactive and creative interactions. However, this change also raises new challenges such as information accuracy and the spread of hoaxes. This research aims to examine the transformation of da'wah in the digital era, understand its influence on traditional da'wah methods, and identify effective strategies in overcoming emerging challenges. The methodology used is qualitative analysis of literature and case studies of digital da'wah practices. The research results show that digital da'wah expands reach and increases congregational engagement through various content formats such as videos, podcasts and mobile applications. However, challenges related to information accuracy and the spread of hoaxes require effective mitigation strategies, including increasing digital literacy and content validation. Da'wah in the digital era requires adapting strategies that not only utilize technology to expand reach, but also ensure the integrity and accuracy of information. This strategy must involve collaboration between da'i, educational institutions, and technology institutions to develop da'wah practices that are innovative and responsive to the dynamics of the times.